2015
DOI: 10.1111/inm.12144
|View full text |Cite
|
Sign up to set email alerts
|

Self‐harm in young people: Prevalence, associated factors, and help‐seeking in school‐going adolescents

Abstract: Adolescent self-harm is recognised as a serious public health problem however there is little reliable comparative data on its prevalence or characteristics or on the extent of help-seeking for self-harm. The aims of this study were to determine the prevalence and associated factors of adolescent self-harm in an urban region in Ireland and to investigate help-seeking behaviours for self-harm. This was a cross-sectional study of 856 school-going adolescents employing an anonymous self-report questionnaire. A li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 53 publications
4
63
0
Order By: Relevance
“…Thus, findings might not generalize to adolescents in general. Help-seeking is considerable low in adolescents engaging in self-injury and risk-taking [54, 55] and particularly low among males. While our outpatient clinic implements specific measures to increase help-seeking (i.e., open clinic) in order to lower the threshold for clinical presentation, adolescents presenting themselves at the clinic might represent a specific group.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, findings might not generalize to adolescents in general. Help-seeking is considerable low in adolescents engaging in self-injury and risk-taking [54, 55] and particularly low among males. While our outpatient clinic implements specific measures to increase help-seeking (i.e., open clinic) in order to lower the threshold for clinical presentation, adolescents presenting themselves at the clinic might represent a specific group.…”
Section: Discussionmentioning
confidence: 99%
“…Community studies have identified that self‐harm is particularly high amongst young people (Doyle et al . ) and presentations to the emergency department (ED) for treatment of self‐harm peak in this cohort (Griffin et al . ).…”
Section: Introductionmentioning
confidence: 95%
“…This definition of self-harm is the operational definition used throughout this current study. In Ireland, a more recent schoolbased study of adolescent self-harm using the same CASE methodology found that 18% of female and 6.4% of male post-primary school students reported a lifetime history of selfharm (Doyle, Treacy & Sheridan, 2015). A common finding in all of the CASE studies was that only a small minority of those who self-harmed actually presented to hospital or sought professional help meaning that most adolescent self-harm was 'hidden' from the health services (Ystgaard et al, 2009;.…”
Section: Introductionmentioning
confidence: 99%